Analysis quality control of white tofu products using the seven tools method in the home industry of Mrs. Menuk. - Insani, Tiara Putri; Riani, Lilia Pasca (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This study analyzes quality control in white tofu production using the Seven Tools method at Tofu Factory Ibu Menuk, Bantul, Yogyakarta.Design/Methode/Approch : A quantitative descriptive approach was used, with data collected through observations and interviews on 250 samples over 15 production cycles.Research Finding : The results show that the most dominant defects were inconsistent texture (36.84%), unpleasant odor (22.49%), dark coloration (21.05%), and mold contamination (19.62%).Control charts indicate that the process remains within statistical control, though fluctuations require monitoring.The Fishbone Diagram analysis identified key defect causes, including raw material quality, machinery, worker skills, environment, and processing methods.Theoritical contribution/Originality : This study contributes to quality management theory and practice by demonstrating how statistical tools improve product consistency and minimize defects.Practitionel/Policy implication : These findings offer practical insights for tofu producers in implementing structured quality control tools to enhance product reliability.Research limitation : Despite its limitation to a single factory, future research could extend to other industries, incorporate advanced monitoring technologies, and explore alternative quality improvement strategies.